On Comparing Cash Flow and Accrual Accounting Models for Use in Equity Valuation: A Response to Lundholm and O'Keefe (CAR, Summer 2001) - Penman, Stephen H. (Contemporary Accounting Research, 2001)
A claim is commonly made that cash flow and accrual accounting methods for valuing equities must always yield equivalent valuations. A recent paper by Lundholm and O'Keefe 2001, for example, claims that, because of this equivalence, there is nothing to be learned from empirical comparison of valuation models. So they dismiss recent research that has shown that accrual accounting residual income models and earnings capitalization models perform, over a range of conditions, better than cash flow or dividend discount models. This paper demonstrates, with examples, that the claim is misguided. Practice inevitably involves forecasting over finite, truncated horizons, and the accounting specified in a model — cash versus accrual accounting in particular — is pertinent to valuation with finite-horizon forecasting. Indeed, the issue of choosing a valuation model is an issue of specifying pro forma accounting, and so, for finite-horizon forecasts, one cannot be indifferent to the accounting.